Shèng Nǚ: Stereotip Perempuan Lajang di China Pada Film “The Last Woman Standing” - Hervita Thalia Pratiwi R; Intan Erwani (Huma: Jurnal Sosiologi, 2023)
China is a country with a strong patriarchal culture and weakens the position of women, so that when women rebel and dare to fight against standards in society, they will be faced with stereotypes and discrimination. This research aims to know the forms of stereotypes experienced by Chinese women in the current era due to the mismatch between their attitudes or life choices and the norms that apply in society. This research examines the stereotypes experienced by single women in China to get the label Shèng Nǚ. The data source for this research is the film “The Last Woman Standing”, as well as other research supporting data sources. The research was conducted using qualitative descriptive methods. The theory used to analyze the research results is existential feminism from Beauvoir (1956). This research found stereotypical forms of single women in China shown in the film "The Last Woman Standing", namely: 1) rejecting marriage; 2) does not need men; and, 3) voters. In fact, women do not reject marriage, it's just that women wait for the right time and the right person for their future. Furthermore, single women are afraid that men are not equal to them, which results in differences in views on life principles and inequality that worsens their situation in the future. Women in this era have the right to make their life choices and not depend on other people, especially men. The results of this research are a reference for the struggle for the existence of single women who are stereotyped and discriminated against by patriarchal communities that think women should be below men.